Phylogeography of the Middle Eastern tree frogs (Hyla, Hylidae, Amphibia) as inferred from nuclear and mitochondrial DNA variation, with a description of a new species - Gvozdík, Václav; Moravec, Jirí; Klütsch, Cornelya; Kotlík, Petr (Molecular phylogenetics and evolution, 2010)
Evolutionary relationships of the tree frogs from the Middle East and the demographic histories of their populations were studied using a combination of mitochondrial and nuclear genes. Hyla savignyi and neighboring populations of H. orientalis (former eastern populations of H. arborea) were the main focus taxa. Within H. savignyi, a deep phylogenetic divergence dated about 8.4Ma was discovered. Southern populations from Yemen, Jordan, southern Syria and extreme north-eastern Israel are hereby described as a new species, H. felixarabica sp. nov. Our study points to a biogeographic connection of the south-western Arabian Peninsula and southern Levant and to the importance of the Dead Sea Rift as a historical barrier geographically separating the new species from H. savignyi. Major genetic breaks revealed within species (H. felixarabica: Yemen vs. Jordan-Syria; H. savignyi sensu stricto: Levant vs. Turkey-Iran) are probably connected to climate changes during the Plio-Pleistocene boundary, while the finer phylogeographic structuring probably resulted from the Quaternary climate oscillations. The Cypriote population of H. savignyi originated from southern Anatolia relatively recently. Hyla orientalis from the southern Black Sea region seems to be genetically quite uniform, although two phylogeographic units with western Turkish and Caucasus-Caspian affinities might be detected. Hyla savignyi and H. orientalis carry signals of population expansions dated to the middle to late Pleistocene, while populations of H. felixarabica seem to have rather been constant in size, which might indicate more stable climatic conditions in the southern regions during the Quaternary.
Keywords: molekulární evoluce; sekvenční seřazení; zeměpis; haplotypy; vznik druhů (genetika); Anura; Humans; Cell Nucleus; Phylogeny; Population Dynamics; Střední východ; mitochondriální DNA; Likelihood Functions; Sequence Analysis, DNA; Geography; žáby; Evolution, Molecular; DNA, Mitochondrial; Middle East; Haplotypes; buněčné jádro; lidé; zvířata; genetická variace; populační dynamika; sekvenční analýza DNA; Genetic Variation; fylogeneze; Bayesova věta; Genetic Speciation; pravděpodobnostní funkce; Animals; Bayes Theorem; Sequence Alignment